Minimally invasive ultrasound‐guided carpal tunnel release: A cadaver study. Issue 2 (11th September 2012) - de la Fuente, Javier; Miguel‐Perez, Maria Isabel; Balius, Ramon; Guerrero, Valentin; Michaud, Johann; Bong, David
Abstract Background. Carpal tunnel syndrome is a common condition frequently requiring surgical intervention. We describe a new minimally invasive surgical technique for carpal tunnel release utilizing ultrasound (US) visualization. Methods. The technique was performed on 20 fresh frozen cadaver specimens. A surgical metallic probe with a "U"‐shaped trough and upward curved distal tip was precisely positioned in the carpal tunnel with US guidance followed by division of the flexor retinaculum (FR) with a "V"‐shaped scalpel. Results. Complete division of the FR was confirmed by US. Dissection performed on the specimens confirmed complete release of FR and absence of neurovascular injury. The distance from the division of the FR to these structures, the "safety margins, " was measured. Conclusions. This new technique for carpal tunnel release appears to combine the safety and efficacy of open carpal tunnel surgery with the advantages of the minimally invasive techniques. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013